Secure data offloading strategy for multi-UAV wireless networks based on minimum energy consumption - Gaofeng CUI; Yuanyuan XU; Shanghong ZHANG; Weidong WANG (Tongxin xuebao)
To solve the problems of ground passive eavesdropping when ground users offload data to the multi-UAV(unmanned aerial vehicle) edge computing network, a secure data offloading strategy that minimized system energy consumption by jointly optimizing user matching and resource allocation was proposed.Considering the constraints of system delay, communication resources and computing resources, the probability of security interruption was used to restrict the security performance of the data offload process.By using block coordinate descent and successive convex approximation algorithm, the user transmission power, offload factor, UAV computing resource allocation and jamming power were jointly optimized.A pair-wise stable user matching algorithm was proposed to minimize the total energy consumption of UAV system.Simulation results demonstrate that the algorithm can realize the safe offloading of data, and has good performance in energy consumption and delay by comparing with the conventional strategies.